Biocomposites Based on Thermoplastic Starch and Granite Sand Quarry Waste - Passaretti, María Gabriela (2019)
Granite stone is a by-product of the rock crushing manufacturing. An industrial waste in powder form that causes health problems and environmental pollution. Fine particles fraction can be used as a partial replacement of sand in concrete manufacture. In this work, an alternative exploitation of this waste fraction is proposed. Granite sand (GS) with particles mean size of ~1 μm was employed as thermoplastic starch (TPS) filler at different concentrations. Biocomposites were obtained by melt-mixing and thermo-compression, achieving translucent and easy to handle films. A good GS dispersion within the matrix was evidenced by SEM. Mineral presence induced a shift of starch’s melting point to higher values and a better thermal resistance. TPS UV absorption capacity was increased ~90% by GS addition. An increment in TPS Young’s modulus and maximum tensile stress of 5 and 3 times, respectively was observed by adding 5 % w/w GS.